Examining the Relationship Between Age and Misconceptions in Electricity among Secondary School Students and the Moderating Role of Gender - Adeniyi Michael Adeduyigbe (Scientia Publica Media, 2025)
Understanding electricity concepts, such as circuits, current, and voltage, presents significant difficulties for secondary school students due to their abstract nature and associated misconceptions. This study examines the relationship between age and misconceptions in understanding these concepts, as well as the moderating role of gender. A cross-sectional, quantitative research design was adopted, utilizing the Electricity Diagnostic Test (EDT) to evaluate 298 secondary school students. The findings reveal no significant relationship between age and misconceptions, indicating that conceptual misunderstandings persist across different age groups. Additionally, gender does not significantly moderate this relationship, suggesting that both male and female students face similar difficulties in learning electricity concepts. These results challenge traditional cognitive development theories, such as Piaget’s, which propose that older students should have a better grasp of abstract concepts. Instead, the findings align with research indicating that misconceptions in physics persist due to instructional methods rather than age-related cognitive development. The study highlights the importance of adopting evidence-based teaching strategies, such as interactive learning and conceptual change approaches, to address misconceptions. This research contributes to physics education by emphasizing the need for gender-inclusive pedagogies and targeted interventions that focus on addressing misconceptions rather than assuming natural conceptual progression. The findings have practical implications for educators and policymakers, advocating for curriculum adjustments that integrate diagnostic assessments and active learning methodologies to enhance conceptual understanding in electricity. Future research should explore additional socio-cultural factors influencing physics learning and assess the long-term impact of instructional interventions on conceptual retention.